Factors influencing hibernation in Harmonia axyridis: Role of the environment and interval timer - Alois Honek; Zdenka Martinkova; Jiří Skuhrovec (Frontiers in Ecology and Evolution, 2022)
From 2014 to 2022, we investigated the length of hibernation in a population of the invasive ladybird Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae) in Central Europe. Adults were collected during the autumn immigration to overwintering sites and placed in an artificial hibernaculum held in an unheated closed shelter. The following spring, the population was monitored for timing of emigration from this hibernaculum. In individual years, massive immigration took place between late September and late October and immigration lasted one to 3 days, each year. The main period of emigration from the hibernaculum (extending from the time that 25% of adults departed the hibernaculum to the time that 75% of the remaining individuals departed) occurred in individual years between mid-April and early May and lasted 8.0 ± 1.3 days (mean ± SE). Massive emigration activity followed a gradual period of increasing temperature. Although the dates of migration in some years, both autumn and spring, ranged over a period of 1 month, the overwintering period (from immigration to emigration of 50% of the population) was similar each year, 185.0 ± 6.3 days (mean ± SE). We hypothesize that the length of overwintering may be fixed by an intrinsic interval timer in H. axyridis adults. The internal timing of the end of hibernation may be advantageous in the cold temperate zone, where H. axyridis adults overwinter in buildings and are thus isolated from external photoperiodic and temperature stimuli that signal the end of the winter season.